The Effect of Organic Fertilizer Types and Phosphate Fertilizer Doses on Growth and Yield of Chili (Capsicum Annum L.) var. Lotanbar - Helti Andraini; Firsta Ninda Rosadi; Vivi Ruslini (JERAMI : Indonesian Journal of Crop Science, 2021)
Red chili plants are one of the important vegetable commodities and have high economic value in Indonesia, most of them are used for household and industrial purposes. The demand for red chili plants is increasing every year so that efforts are needed to increase the productivity of red chili plants. The objectives of study to determine (1) the effect of the interaction between the application of organic fertilizers and inorganic fertilizers on the growth and yield of red chili plants, (2) the effect of the type of organic fertilizer and the correct dosage of inorganic fertilizers on the growth and yield of red chili plants. The research was conducted from January to May 2019 in Sumani village, X Koto Singkarak sub District, Solok District with a height of ± 400 meters above sea level. The design was used a factorial design in a Randomized Block Design (RBD) with 2 factors. The first factor is the use of organic fertilizers derived from cow manure (A1) and straw compost (A2). The second factor is the use of SP-36 fertilizer as a source of phosphate at a dose of 10 g/plant (B1), a dose of 30 g/plant (B2), and a dose of 50 g/plant (B3), each treatment consisting of four sample plants. Data from the observations were carried out by analysis of variance, if the obtained F count was greater than F table 5% followed by a further test of Duncan New Multiple Range Test (DNMRT) at the 5% real level. Parameters were observed: plant height, stem diameter, number of fruits, fruit length, fruit weight per plant, and yield of chili per hectare. The results showed that: (1) The results showed that the application of organic fertilizers was better for the growth and yield of Lotanbar chili plants. (2) The provision of cow manure can increase the growth of plant height, fruit length, fruit weight per plant and plant yield per hectare (3) There is no interaction between types of organic fertilizers and the dosage of phosphate fertilizers.